A laser ablation technique maps differences in elemental composition in roots of two barley cultivars subjected to salinity stress. (12th December 2019) - Shelden, Megan C.; Gilbert, Sarah E.; Tyerman, Stephen D.
Summary: In saline soils, high levels of sodium (Na + ) and chloride (Cl − ) ions reduce root growth by inhibiting cell division and elongation, thereby impacting on crop yield. Soil salinity can lead to Na + toxicity of plant cells, influencing the uptake and retention of other important ions [i.e. potassium (K + )] required for growth. However, measuring and quantifying soluble ions in their native, cellular environment is inherently difficult. Technologies that allow in situ profiling of plant tissues are fundamental for our understanding of abiotic stress responses and the development of tolerant crops. Here, we employ laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) to quantify Na, K and other elements [calcium (Ca), magnesium (Mg), sulphur (S), phosphorus (P), iron (Fe)] at high spatial resolution in the root growth zone of two genotypes of barley ( Hordeum vulgare ) that differ in salt‐tolerance, cv. Clipper (tolerant) and Sahara (sensitive). The data show that Na + was excluded from the meristem and cell division zone, indicating that Na + toxicity is not directly reducing cell division in the salt‐sensitive genotype, Sahara. Interestingly, in both genotypes, K + was strongly correlated with Na + concentration, in response to salt stress. In addition, we also show important genetic differences and salt‐specific changes in elemental composition in the root growth zone. These results show that LA‐ICP‐MS can be used for fine mapping of soluble ions (i.e. Na + and K + ) in plant tissues, providing insight into the link between Na + toxicity and root growth responses to salt stress. Significance Statement: Understanding sodium toxicity at the cellular and tissue level is imperative for the development of salt‐tolerant crops. Due to the soluble nature of sodium (and other important ions), quantifying these at the cellular and tissue level is inherently difficult. To address this challenge, laser ablation‐inductively coupled plasma‐mass spectrometry was used to quantify soluble ions at high spatial resolution in barley roots, providing a tool to better understand adaptation to salinity stress in crop plants.